ASSESSING CARPAL TUNNEL SYNDROME AMONG ADMINISTRATIVE STAFF OF A HIGHER LEARNING INSTITUTION: A PRELIMINARY STUDY - Muhammad Kamil Che Hasan (Belitung Raya Foundation, 2020)
Background: Repeated hand and wrist movements increase the risk of carpal tunnel syndrome (CTS). The administrative staff is one of the high-risk classes that repeatedly involve the execution of identical tasks.